Genome‐wide insights into introgression and its consequences for genome‐wide heterozygosity in the Mytilus species complex across Europe. (24th April 2020) - Vendrami, David L. J.; De Noia, Michele; Telesca, Luca; Brodte, Eva‐Maria; Hoffman, Joseph I.
Abstract: The three mussel species comprising the Mytilus complex are widespread across Europe and readily hybridize when they occur in sympatry, resulting in a mosaic of populations with varying genomic backgrounds. Two of these species, M. edulis and M. galloprovincialis, are extensively cultivated across Europe, with annual production exceeding 230, 000 tonnes. The third species, M.   trossulus, is considered commercially damaging as hybridization with this species results in weaker shells and poor meat quality. We therefore used restriction site associated DNA sequencing to generate high‐resolution insights into the structure of the Mytilus complex across Europe and to resolve patterns of introgression. Inferred species distributions were concordant with the results of previous studies based on smaller numbers of genetic markers, with M. edulis and M. galloprovincialis predominating in northern and southern Europe respectively, while introgression between these species was most pronounced in northern France and the Shetland Islands. We also detected traces of M. trossulus ancestry in several northern European populations, especially around the Baltic and in northern Scotland. Finally, genome‐wide heterozygosity, whether quantified at the population or individual level, was lowest in M. edulis, intermediate in M. galloprovincialis, and highest in M. trossulus, while introgression was positively associated with heterozygosity in M. edulis but negatively associated with heterozygosity in M. galloprovincialis . Our study will help to inform mussel aquaculture by providing baseline information on the genomic backgrounds of different Mytilus populations across Europe and by elucidating the effects of introgression on genome‐wide heterozygosity, which is known to influence commercially important traits such as growth, viability, and fecundity in mussels.